Sintering apparatus with die liner with increased thickness

By using high-carbon material punches and graphite layer die heads in the sintering device, combined with discharge plasma sintering technology, the problem of difficulty in preparing large-sized ceramic bodies in the prior art is solved, and the multiple performance improvements of the ceramic bodies are achieved.

CN119894654APending Publication Date: 2025-04-25HERAEUS CONAMIC NORTH AMERICA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052430.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-08-04
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing discharge plasma sintering (SPS) technology is difficult to effectively prepare large-size ceramic bodies, and there are problems such as high energy demand, high waste rate, high fracture sensitivity, high internal stress, low mechanical strength, uneven density, poor etch resistance and high surface roughness.

Method used

An improved sintering device is employed, which comprises a device having a sintering chamber defined by the inner surfaces of the first punch, the second punch and the die head. The punch is made of high carbon material, capable of applying high pressure and high current, and the inner surface of the die is coated with a graphite layer to improve conductivity and density uniformity.

Benefits of technology

It has achieved the preparation of ceramic bodies with reduced energy demand, low waste rate, low fracture sensitivity, low internal stress, high mechanical strength, high density, density uniformity, etch resistance and low surface roughness, which is suitable for the production of large-size ceramic bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894654A_ABST
    Figure CN119894654A_ABST
Patent Text Reader

Abstract

The present invention generally relates to sintering under pressure and using electrical current, generally referred to as spark plasma sintering (SPS). Particular aspects of the invention relate to a sintering apparatus, a sintering method, a ceramic body product, an assembly comprising a ceramic body, and the use of a graphitic layer in a sintering method. The invention relates to a device having a sintering chamber (013) which is delimited by the following device components: i. A first punch surface (004) of a first punch (003); ii. A second punch surface (007) of a second punch (008); and iii. An inner surface (005) of the die (006); wherein: the punch (003, 008) is adapted and arranged to apply a pressure of at least 1 MPa to a target in the sintering chamber along a compression axis (011); the first punch and the second punch are connected to an electrical power source (012) adapted and arranged to provide a current of at least 5 kA; the first punch and the second punch comprise at least 50 wt% carbon, based on the total weight of the punches; the sintering chamber has a cross-sectional width W of at least 300 mm perpendicular to the compression axis; wherein a layer [delta] of carbon material C [delta] is present at at least a portion of the inner surface of the die, the layer [delta] having an average thickness D [delta] determined on the inner surface of the die, where D [delta] is in the range of 1.1 mm to 8 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to sintering under pressure and using an electric current, commonly referred to as spark plasma sintering (SPS). Particular aspects of the present invention relate to sintering apparatus, sintering methods, ceramic body products, components including ceramic bodies, and the use of graphite layers in sintering methods. Background Art

[0002] Sintering methods provide a way to form a body from particles by applying heat and pressure. In a method generally referred to as spark plasma sintering (SPS), heating is achieved using an electric current. Spark plasma sintering methods in the prior art have been applied to a variety of materials. Existing literature focuses on small-scale systems, providing access to components with physical extensions of up to about 150 mm. Eugene A. Olevsky et al. evaluated the problem of using SPS to prepare larger components from a theoretical perspective in the following literature: "Fundamental Aspects of Spark Plasma Sintering: I. Experimental Analysis of Scalability" (J. Am. Ceram. Soc., 95[8], 2406 to 2413 (2012)) and "Fundamen-tal Aspects of Spark Plasma Sintering: II. Experimental Analysis of Scalability" (J. Am. Ceram. Soc., 95[8], 2414 to 2422 (2012)). Several potential challenges and complications associated with large-scale systems were identified. Summary of the invention

[0003] It is an object of the present invention to provide an improved process for preparing ceramic bodies. It is a particular object of the present invention to provide an improved process for preparing ceramic bodies of increased size.

[0004] It is an object of the present invention to provide an improved process for producing ceramic bodies having a reduced energy requirement.

[0005] It is an object of the present invention to provide an improved process for producing ceramic bodies having a reduced scrap rate.

[0006] It is an object of the present invention to provide an improved process for producing ceramic bodies having reduced fracture sensitivity.

[0007] It is an object of the present invention to provide an improved process for producing ceramic bodies having reduced internal stresses.

[0008] It is an object of the present invention to provide an improved process for producing ceramic bodies having increased mechanical strength.

[0009] It is an object of the present invention to provide an improved process for producing ceramic bodies having increased density.

[0010] It is an object of the present invention to provide an improved process for producing ceramic bodies having increased density uniformity.

[0011] It is an object of the present invention to provide an improved process for producing ceramic bodies having increased etching resistance.

[0012] It is an object of the present invention to provide an improved process for producing ceramic bodies having reduced surface roughness.

[0013] The object of the present invention is to provide an apparatus for carrying out the above-mentioned improved method.

[0014] Any embodiment of the present invention contributes to at least partially achieving at least one of the above-mentioned objects.

[0015] A first embodiment of the invention is a device having a sintering chamber, which is defined by the following device components:

[0016] i. a first punch surface of a first punch;

[0017] ii. a second punch surface of a second punch; and

[0018] iii. the inner surface of the die;

[0019] in:

[0020] The punch is adapted and arranged to apply a pressure of at least 1 MPa, preferably at least 5 MPa, more preferably at least 10 MPa, most preferably at least 15 MPa to the target in the sintering chamber along the compression axis. The punch may be adapted and arranged to apply a pressure of up to 80 MPa or even higher;

[0021] The first punch and the second punch are connected to an electrical power source adapted and arranged to provide a current of at least 5 kA, preferably at least 10 kA, more preferably at least 50 kA, most preferably at least 60 kA. The electrical power source may be adapted and arranged to provide a current of up to 100 kA or even more;

[0022] The first punch and the second punch comprise at least 50 wt %, preferably at least 90 wt %, more preferably at least 95 wt %, most preferably at least 99 wt % carbon, based on the total weight of the punch;

[0023] The sintering chamber has a cross-sectional width W perpendicular to the compression axis of at least 300 mm, preferably at least 500 mm, more preferably at least 700 mm. W may be up to 2000 mm or more. It is preferably not more than 1500 mm, more preferably not more than 900 mm;

[0024] wherein a carbon material C is present at at least a portion of the inner surface of the die head δ A layer δ having an average thickness D determined on the inner surface of the die δ ,

[0025] Where D δ In the range of 1.1 mm to 8 mm, preferably in the range of 1.3 mm to 4 mm, more preferably in the range of 1.5 mm to 3 mm, and further preferably in the range of 1.9 mm to 2.5 mm.

[0026] In a preferred embodiment of the device, the width W is at least 500 mm and the thickness D δ At least 1.5 mm, preferably at least 1.8 mm, more preferably at least 1.93 mm. This preferred embodiment is the second embodiment of the present invention, which is preferably dependent on the first embodiment of the present invention.

[0027] In another preferred embodiment of the device, the width W is less than 500 mm and the thickness D δ At most 1.8 mm, preferably at most 1.6 mm, more preferably at most 1.3 mm. This preferred embodiment is the third embodiment of the present invention, which is preferably dependent on the first or second embodiment of the present invention.

[0028] In a preferred embodiment of the device, the thickness D of the layer δ determined on the inner surface of the die is δ The standard deviation is in the range of 0.01mm to 0.08mm, preferably in the range of 0.02mm to 0.06mm, more preferably in the range of 0.03mm to 0.05mm. This preferred embodiment is the fourth embodiment of the present invention, and this fourth embodiment preferably depends on any one of the first to third embodiments of the present invention.

[0029] In a preferred embodiment of the device, layer δ consists of 2 or more, preferably 2 to 10, or 2 to 8 or 2 to 6 stacked sublayers. This preferred embodiment is the fifth embodiment of the present invention, which preferably depends on any one of the first to fourth embodiments of the present invention.

[0030] In a preferred embodiment of the device, the chamber has a diameter D C , and the diameter DC With layer D δ The average thickness ratio D C :D δ In the range of 100: 1 to 250: 1, preferably in the range of 120: 1 to 230: 1, more preferably in the range of 130: 1 to 210: 1. This preferred embodiment is the sixth embodiment of the present invention, and the sixth embodiment preferably depends on any one of the first to fifth embodiments of the present invention.

[0031] In a preferred embodiment of the device, the two punches (003, 008) and the die are at least partially present in a vacuum chamber or in a non-oxidizing atmosphere or both. This preferred embodiment is the seventh embodiment of the present invention, and the seventh embodiment preferably depends on any one of the first to sixth embodiments of the present invention.

[0032] In a preferred embodiment of the device, the electrical power source is adapted and arranged to supply a DC voltage.This preferred embodiment is an eighth embodiment of the invention, which preferably depends on any one of the first to seventh embodiments of the invention.

[0033] In a preferred embodiment of the device, one or both of the following are satisfied:

[0034] a. There is a carbon material C at at least a portion of the first punch surface ε a layer ε, which preferably has an average thickness in the range of 1.1 mm to 8 mm;

[0035] b. There is a carbon material C at at least a portion of the second punch surface θ The layer θ preferably has an average thickness in the range of 1.1 mm to 8 mm.

[0036] This preferred embodiment is the ninth embodiment of the present invention, and this ninth embodiment preferably depends on any one of the first to eighth embodiments of the present invention. In one aspect of the ninth embodiment, all possible combinations of features a. and b. are preferred aspects of this embodiment. These combinations are, for example, a; b; a+b.

[0037] In a preferred embodiment of the device, one or more of the following are met:

[0038] a. The first punch comprises at least 99 wt % carbon based on the total weight of carbon atoms in any chemical form and the total weight of the first punch;

[0039] b. The second punch comprises at least 99 wt % carbon based on the total weight of carbon atoms in any chemical form and the total weight of the second punch;

[0040] c. The die comprises at least 99 wt % carbon, based on the total weight of carbon atoms in any chemical form and the total weight of the die;

[0041] d. Layer δ comprises at least 99 wt% carbon, based on the total weight of carbon atoms in any chemical form and the total weight of layer δ.

[0042] This preferred embodiment is the tenth embodiment of the invention, which is preferably dependent on any one of the first to ninth embodiments of the invention. In one aspect of the tenth embodiment, all possible combinations of features a. to d. are preferred aspects of this embodiment. These combinations are, for example, a; b; c; d; a+b; a+c; a+d; b+c; b+d; c+d; a+b+c; a+b+d; a+c+d; b+c+d; a+b+c+d.

[0043] In a preferred embodiment of the device, the die is made of a carbon material Cγ and satisfies one or more of the following:

[0044] C δ and C γ With different anisotropy values,

[0045] B C δ and C γ having different specific conductivities determined in a direction parallel to the compression axis,

[0046] C δ and C γ having different specific conductivities determined in a direction perpendicular to the inner surface,

[0047] dC δ and C γ having different specific thermal expansion rates determined in a direction parallel to the compression axis,

[0048] eC δ and C γ having different specific thermal expansion rates determined in a direction perpendicular to the inner surface,

[0049] f. The first carbon material and the second carbon material have different ash contents as determined by ASTM C-561.

[0050] This preferred embodiment is the eleventh embodiment of the invention, which is preferably dependent on any one of the first to tenth embodiments of the invention. In one aspect of the eleventh embodiment, all possible combinations of features a. to f. are preferred aspects of this embodiment. These combinations are, for example, a; b; c; d; e; f; a+b; a+c; a+d; a+e; a+f; b+c; b+d; b+e; b+f; c+d; c+e; c+f; d+e; d+f; e+f; a+b+c; a+b+d; a+b+e; a+b+f; a+c+d; a+c+e; a+c+f; a+d+e; a+d+f; a+e+f; b+c+d; b+c+e; b+c+f; b+d+e; b+d+f; b+e+f; c+d+e; c+d+f; c+e+f; d+ e+f;a+b+c+d;a+b+c+e;a+b+c+f;a+b+d+e;a+b+d+f;a+b+e+f;a+c+d+e;a+c+d+f;a+c+e+f;a+d+e+f;b+c+d+e;b+c+d+ f; b+c+e+f; b+d+e+f; c+d+e+f; a+b+c+d+e; a+b+c+d+f; a+b+c+e+f; a+b+d+e+f; a+c+d+e+f; b+c+d+e+f; a+b+c+d+e+f.

[0051] A twelfth embodiment of the present invention is a method for preparing a ceramic body, the method comprising the steps of:

[0052] a. Providing multiple particles;

[0053] b. Providing a device according to the present invention;

[0054] c. introducing the particles into the sintering chamber of the apparatus;

[0055] d. applying a pressure P in the range of 1 MPa to 80 MPa and an electric current I in the range of 1 kA to 100 kA, preferably in the range of 5 kA to 100 kA, more preferably in the range of 10 kA to 100 kA, even more preferably in the range of 50 kA to 100 kA, and further preferably in the range of 60 kA to 100 kA, to obtain the ceramic body.

[0056] The device provided in this twelfth embodiment is preferably a device according to any one of the first to eleventh embodiments of the present invention.

[0057] In a preferred embodiment of the method, the particles contain at least 30% by weight, preferably at least 40% by weight, more preferably at least 45% by weight of yttrium in any chemical form, based on the total mass of yttrium atoms and the total mass of the particles. This preferred embodiment is the thirteenth embodiment of the invention, which is preferably dependent on the twelfth embodiment of the invention.

[0058] In a preferred embodiment of the method, the average thickness D after step d is δ Divide by the thickness D before step a. δ The value of is preferably at least 0.8, more preferably at least 0.9, more preferably at least 0.95. This preferred embodiment is the fourteenth embodiment of the present invention, and the fourteenth embodiment is preferably dependent on the twelfth or thirteenth embodiment of the present invention.

[0059] A fifteenth embodiment of the present invention is a ceramic body obtainable by a method according to the present invention. The method is preferably according to any one of the twelfth to fourteenth embodiments.

[0060] In a preferred embodiment of the ceramic body, at least one or all of the following are satisfied for the ceramic body:

[0061] a. The value of density divided by theoretical density is less than 1.0;

[0062] b. an average grain size of less than 5 μm, preferably less than 4.5 μm, more preferably less than 4 μm, and further preferably from 1 μm to 3 μm;

[0063] c. The standard deviation of the average grain size distribution is in the range of 1.2±2 μm to 2.8±2 μm, preferably in the range of 1.6±2 μm to 2.4±2 μm, and more preferably in the range of 1.8±2 μm to 2.2±2 μm.

[0064] This preferred embodiment is the sixteenth embodiment of the present invention, and this sixteenth embodiment is preferably dependent on the fifteenth embodiment of the present invention. In one aspect of the sixteenth embodiment, all possible combinations of features a. to c. are preferred aspects of this embodiment. These combinations are, for example, a; b; c; a In the sixteenth embodiment, in one aspect of feature a., the value of density divided by theoretical density is preferably at least 0.9, more preferably at least 0.95, and further preferably at least 0.99.

[0065] A seventeenth embodiment of the present invention is an assembly comprising a ceramic body according to the present invention, preferably a ceramic body according to the fifteenth or sixteenth embodiment.

[0066] In a preferred embodiment of the assembly, the assembly is selected from the group consisting of:

[0067] a. Plasma etcher,

[0068] b. Plasma processing chamber (etching or deposition method),

[0069] c. Wear-resistant plates for load bearing,

[0070] d. Mill lining of grinding mill.

[0071] The preferred embodiment is the eighteenth embodiment of the present invention, and the eighteenth embodiment is preferably dependent on the seventeenth embodiment of the present invention.

[0072] A nineteenth embodiment of the present invention is the use of a graphite layer having a thickness in the range of 1.1 mm to 8 mm, preferably in the range of 1.3 mm to 4 mm, more preferably in the range of 1.5 mm to 3 mm, and further preferably in the range of 1.8 mm to 2.5 mm for preparing a ceramic body having an extension of at least 300 mm by spark plasma sintering. DETAILED DESCRIPTION

[0073] sintering

[0074] The present invention relates to a sintering method. A preferred sintering method produces a body from particles by applying pressure and heat. The heating is preferably performed by applying an electric current.

[0075] The preferred sintering increases the density of the plurality of particles to produce a body. The body preferably has a higher density than the plurality of particles.

[0076] Preferred sintering produces a product body having a density of at least 95%, preferably at least 99%, more preferably at least 99.9% of its theoretical density.

[0077] Device

[0078] The device of the present invention is suitable and arranged for sintering particles to produce a body. The device comprises at least a first punch, a second punch and a die. The device has a sintering chamber.

[0079] Sintering chamber

[0080] The device of the present invention has a sintering chamber. The sintering chamber is preferably suitable for and arranged to accommodate a plurality of particles. The sintering chamber is preferably defined by a first punch surface of the first punch, a second punch surface of the second punch, and an inner surface of the die. The sintering chamber may be defined only by the first punch surface, the second punch surface, and the inner surface, or may be additionally defined by one or more further surfaces. The sintering chamber is preferably defined only by the first punch surface, the second punch surface, and the inner surface.

[0081] The sintering chamber may have one or more planes of symmetry or one or more axes of symmetry or both. The sintering chamber may have the form of a volume of revolution. The sintering chamber may be cylindrical.

[0082] Punch

[0083] The device of the present invention has a first punch and a second punch. The first punch has a first punch surface defining a sintering chamber. The second punch has a second punch surface defining a sintering chamber. Preferably, one or both of the punch surfaces are substantially flat.

[0084] The punch is preferably adapted and arranged to apply a force to the target in the sintering chamber, preferably to generate an elevated pressure in the sintering chamber. The punch is preferably adapted and arranged to generate a pressure of at least 1 MPa, preferably at least 5 MPa, more preferably at least 10 MPa, most preferably at least 15 MPa in the sintering chamber. The punch may be adapted and arranged to apply a pressure of up to 80 MPa or even higher.

[0085] The first punch and the second punch are preferably positioned vertically above and below the sintering chamber, respectively.The first punch and the second punch are preferably adapted and arranged to move along the compression axis.

[0086] The punch is preferably electrically conductive. The punch is preferably adapted and arranged to provide a current of at least 5 kA, preferably at least 10 kA, more preferably at least 50 kA, most preferably at least 60 kA across the sintering chamber. The electrical power source may be adapted and arranged to provide a current of up to 100 kA or even greater.

[0087] The punch is preferably made of a carbon material, most preferably graphite. The punch preferably comprises at least 95 wt% carbon, more preferably at least 99 wt%, still more preferably at least 99.5 wt% carbon. The punch may comprise one or more selected from: a layer and a region; made of a material other than carbon.

[0088] Die head

[0089] The device of the present invention has a die head. The die head has an inner surface defining a sintering chamber.

[0090] In one embodiment, the die is electrically conductive. Preferably, the die has anisotropic conductivity, preferably with a material orientation axis substantially aligned with the compression axis.

[0091] In one embodiment, the die comprises one or more elements selected from Group 14 of the periodic table. Group 14 elements are sometimes also referred to as Group IVA elements or Group 4A elements. The die preferably comprises one or more selected from the group consisting of C, Si, Ge, Sn and Pb, preferably selected from C, Si, Ge and Sn, most preferably selected from C and Si. C is the most preferred Group 14 element. In one aspect of this embodiment, the die comprises 50 wt % or more, more preferably 90 wt % or more, most preferably 95 wt % or more of the Group 14 element, based on the total weight of the die.

[0092] In one embodiment, the die comprises at least 50 wt %, preferably 90 wt % or more, more preferably 95 wt % or more, most preferably 99 wt % or more C, based on the total weight of the die. In one aspect of this embodiment, the die additionally comprises one or more additional Group 14 elements, preferably selected from Si, Ge, Sn and Pb, more preferably selected from Si, Ge and Sn, still more preferably selected from Si and Ge, most preferably Si. The other Group 14 elements are preferably present in a total content of at least 0.1 wt %, more preferably at least 1 wt %, most preferably at least 2 wt %. In this embodiment, elements other than C, Si, Ge, Sn and Pb are preferably present in a total content of not more than 1 wt %, more preferably not more than 0.5 wt %, most preferably not more than 0.1 wt %.

[0093] The die can be a single piece or multiple pieces, preferably a single piece. Preferably, the die is a single continuous body, more preferably a single cylinder. The die is preferably present in 2 to 10 pieces, more preferably 2 to 5 pieces, still more preferably 2 to 3 pieces, most preferably 2 pieces.

[0094] The die head may have one or more planes of symmetry or one or more axes of symmetry or both. The sintering chamber may have the form of a volume of revolution. The sintering chamber may be hollow cylindrical.

[0095] The die is preferably made of a carbon material, most preferably graphite.

[0096] orientation

[0097] The device of the invention has a compression axis. The device is preferably adapted and arranged to apply a force to the sintering chamber in the direction of the compression axis.

[0098] Preferably, the first punch is movable along the compression axis. Preferably, the second punch is movable along the compression axis. Preferably, both punches are movable along the compression axis.

[0099] In one embodiment, the compression axis is substantially vertical, preferably, wherein the first punch is positioned above the second punch. In one aspect of this embodiment, the first punch surface is preferably the lower surface of the first punch. In another aspect of this embodiment, the first punch surface is substantially horizontal. In another aspect of this embodiment, the second punch surface is preferably the upper surface of the second punch. In another aspect of this embodiment, the second punch surface is substantially horizontal.

[0100] The sintering chamber is preferably adapted and arranged to accommodate a plurality of particles.

[0101] layer

[0102] In the apparatus of the present invention, the carbon material layer exists at at least a portion of the inner surface of the die.

[0103] In one embodiment, based on the total area of ​​the inner surface of the die, the layer is present at 20% or more of the inner surface of the die, preferably 50% or more, more preferably 90% or more, and most preferably 95% or more. It is most preferred to have the layer present on substantially the entire inner surface of the die.

[0104] In one embodiment, the layer lines the interior surface of the die, preferably lines substantially the entire surface of the die.

[0105] In one embodiment, a first gap exists between the inner surface of the die and the first punch, and the layer exists in at least a portion of the gap, preferably in substantially the entire gap.

[0106] In one embodiment, a second gap exists between the inner surface of the die and the second punch, and the layer exists in at least a portion of the gap, preferably in substantially the entire gap.

[0107] In one embodiment, the device comprises additional layers.

[0108] The layer may be a single layer, or may have at least two stacked sub-layers. The layer preferably has at least two stacked sub-layers, preferably 2 to 20 stacked sub-layers. The layer or any sub-layer may be present on a portion of the inner periphery of the die, or on substantially the entire inner periphery of the die, or on the entire inner periphery of the die and at least partially overlap itself.

[0109] The layer is preferably close to the inner surface of the die, more preferably in physical contact with the inner surface of the die. The layer can be a piece that is not integrally connected to the inner surface of the die. This is especially the case before the sintering process. The layer can be integrally connected to the inner surface of the die. This is especially the case after the sintering process.

[0110] The thickness of the layer was determined as an average value over the entire inner surface of the die.

[0111] The layer may be a graphite foil. The graphite foil preferably has a plurality of 2D platelets. The graphite foil is preferably arranged to form a roll.

[0112] The layer preferably has an ash content of less than 1 wt.-%, more preferably less than 0.5 wt.-%, still more preferably less than 0.4 wt.-%.

[0113] product

[0114] The product of the present invention is a ceramic body. The ceramic body preferably has a higher density than the plurality of particles. Preferably the body is a continuous object. Preferably the density of the body divided by the theoretical density is at least 0.9, preferably at least 0.95, more preferably at least 0.99.

[0115] Preferred ceramics are inorganic materials. Preferred ceramics are non-metallic. Some preferred ceramics are oxides, nitrides, carbides, or combinations thereof. Preferred ceramics are refractory materials.

[0116] Preferred oxide ceramics may be oxides of a single element, or mixed oxides of more than one element. Oxide ceramics may contain some nitride or carbide content or both. Oxide ceramics may be nitride-free or carbide-free or both. Preferred ceramic oxides may be stoichiometric or non-stoichiometric. Stoichiometric oxides preferably have integer ratios between the atomic numbers of their constituent elements. Oxide ceramics may contain two or more element groupings, each element in stoichiometric ratios to each other element of its own grouping, but in non-stoichiometric ratios to each element of other groupings.

[0117] Preferred nitride ceramics may be nitrides of a single element, or mixed nitrides of more than one element. Nitride ceramics may contain some oxide or carbide content or both. Nitride ceramics may be oxide-free or carbide-free or both. Preferred ceramic nitrides may be stoichiometric or non-stoichiometric. Stoichiometric nitrides preferably have integer ratios between the atomic numbers of their constituent elements. Nitride ceramics may contain two or more element groupings, each element in a stoichiometric ratio to each other element of its own grouping, but in a non-stoichiometric ratio to each element of the other groupings.

[0118] Preferably, the carbide ceramic may be a carbide of a single element, or a mixed carbide of more than one element. The carbide ceramic may contain some oxide or nitride content or both. The carbide ceramic may be free of oxides or free of nitrides or free of both. Preferably, the ceramic carbide may be stoichiometric or non-stoichiometric. Stoichiometric carbides preferably have an integer ratio between the atomic numbers of their constituent elements. The carbide ceramic may contain two or more element groupings, each element being in a stoichiometric ratio with each other element of its own grouping, but in a non-stoichiometric ratio with each element of the other groupings.

[0119] The preferred constituent element of the ceramic is yttrium. Based on the total weight of the ceramic, the ceramic may contain at least 20% by weight, preferably at least 30% by weight, more preferably at least 40% by weight, and most preferably at least 45% by weight of yttrium atoms. The yttrium content may be as high as 50% by weight, or even higher. Preferred yttrium-containing ceramics contain oxides. Preferred yttrium-containing ceramics are oxide ceramics, preferably mixed oxide ceramics, which contain atoms of one or more elements different from yttrium and oxygen. Mixed oxide ceramics are generally quantified according to the content of the simple oxides required to prepare them. Based on the total weight of the ceramic, preferred yttrium-containing mixed oxide ceramics contain at least 20% by weight, preferably at least 30% by weight, more preferably at least 40% by weight, and most preferably at least 45% by weight of yttrium oxide. The yttrium content may be as high as 50% by weight, or even higher.

[0120] In addition to oxygen, nitrogen and carbon, some preferred elements present in the ceramic are one or more elements selected from the list consisting of yttrium, zirconium, aluminum, titanium, silicon, boron, phosphorus and beryllium. These elements can be components of oxides, nitrides, carbides or combinations thereof.

[0121] Oxygen-containing ceramics are usually quantified according to the amount of simple oxides required to prepare them. Some preferred oxide components are silicon dioxide, boron oxide, beryllium oxide, yttrium oxide, aluminum oxide, zirconium oxide, titanium oxide, silicon dioxide, quartz, calcium oxide, cerium oxide, nickel oxide, copper oxide, strontium oxide, scandium oxide, samarium oxide, hafnium oxide, vanadium oxide, niobium oxide, tungsten oxide, manganese oxide, tantalum oxide, terbium oxide, europium oxide, neodymium oxide, yttrium aluminate oxide, zirconium aluminate oxide, lanthanum oxide, lutetium oxide, and erbium oxide.

[0122] Some preferred mixed oxides are one or more selected from the group consisting of zirconium silicate oxide, hafnium aluminate oxide, hafnium silicate oxide, titanium silicate oxide, lanthanum silicate oxide, lanthanum aluminate oxide (LAO), yttrium silicate oxide, titanium silicate oxide, tantalum silicate oxide, oxynitride, barium titanate, lead titanate and lead zirconate titanate.

[0123] Nitrogen-containing ceramics are usually quantified according to the amount of simple nitride required to make them. Some preferred nitride components are one or more selected from the group consisting of silicon nitride, titanium nitride, yttrium nitride, aluminum nitride, boron nitride, beryllium nitride, and tungsten nitride.

[0124] Carbon-containing ceramics are usually quantified according to the amount of simple carbide required to make them. Some preferred carbide components are silicon carbide, tungsten carbide, chromium carbide, vanadium carbide, niobium carbide, molybdenum carbide, tantalum carbide, titanium carbide, zirconium carbide, hafnium carbide, and boron carbide.

[0125] The ceramic may comprise one or more borides. Some preferred boride components of the ceramic are one or more selected from the group consisting of: molybdenum boride, chromium boride, hafnium boride, zirconium boride, tantalum boride and titanium boride or titanium diboride.

[0126] Some preferred ceramic substances are one or more selected from the group consisting of: sapphire, alumina, yttrium aluminum monoclinic (YAM) (preferably Y4Al2O9), yttrium aluminum garnet (YAG) (preferably Y3Al5O 12 ), yttrium aluminum perovskite (YAP) (preferably YAlO3), cordierite, mullite, magnesium aluminum spinel, zirconia, erbium aluminum garnet (EAG), yttrium oxynitride, silicon oxynitride and forsterite.

[0127] Starting Materials

[0128] According to the present invention, a plurality of particles in a sintering chamber may be transformed into a body by applying pressure and electric current.

[0129] The granules may have the same chemical composition as the product. The preferred chemical composition of the product is also the preferred chemical composition of the granules.

[0130] The preferred size of the particles is in the range of 0.1 μm to 20 μm.

[0131] Method conditions

[0132] The sintering of the particles is carried out under pressure. A pressure of at least 1 MPa, preferably at least 5 MPa, more preferably at least 10 MPa is applied to the particles in the sintering chamber. The applied pressure may be in the range of 15 MPa to 30 MPa. Pressures up to about 80 MPa or even higher may be applied.

[0133] The sintering of the particles is carried out with the application of an electric current. Preferably, a current of at least 5 kA, more preferably at least 10 kA, more preferably at least 50 kA is applied across the sintering chamber. Currents up to 100 kA or even greater may be applied.

[0134] The method is preferably carried out in a non-oxidizing atmosphere. The method can be carried out in a vacuum, with the gas pressure around the device being less than 10 mPa, preferably less than 5 mPa, more preferably less than 1 mPa. The method can be carried out in an inert atmosphere, preferably argon.

[0135] Technology Application

[0136] Ceramic bodies can be used in various technical applications. Some specific applications are one or more selected from the list consisting of: plasma etcher, plasma processing chamber (etching or deposition process), wear plates for load bearings or mill linings for grinding mills.

[0137] Electric power source

[0138] The electrical power source is preferably adapted and arranged to generate Joule heating in the plurality of particles. The electrical power source may be an alternating current, a pulsed direct current or a continuous direct current. Continuous direct current is preferred.

[0139] Attached photos

[0140] The invention will now be explained in more detail with the aid of the following figures.

[0141] Figure 1 is a cross-sectional side view of a device according to the present invention.

[0142] Figure 2 yes Figure 1 Cross-sectional side view of the apparatus with the chamber loaded and ready for sintering.

[0143] Figure 3 The steps of a method for preparing a ceramic body are shown.

[0144] Figure 4 A cutaway cross section of a sintering chamber is shown.

[0145] Figure 5a and Figure 5b The core test adopted in this paper is shown. BRIEF DESCRIPTION OF THE DRAWINGS

[0146] Figure 1004 and 007 are cross-sectional side views of a device according to the present invention. The device comprises a first punch 003 having a first punch surface 004 and a second punch 008 having a second punch surface 007. Punches 003 and 008 are made of solid graphite. Punch surfaces 004 and 007 are also made of graphite. The first punch 003 is positioned above the second punch 008. The first punch 003 is oriented so that the first punch surface 004 is horizontal and facing downward. The first punch 003 can be moved in the vertical direction by a first push device 001 connected via a first piston 002. The second punch 008 is oriented so that the second punch surface 007 is horizontal and facing upward. The second punch 008 can be moved in the vertical direction by a second push device 010 connected via a second piston 009. The first punch surface 004 and the second punch surface 007 can therefore move toward each other in the direction of the compression axis 011. The device has a die 006 shaped as a hollow graphite cylinder having an inner surface 005. The device has an electric power source 012, which is suitable and arranged to supply a DC current of up to 20 kA and is connected to a first punch 003 and a second punch 008. The sintering chamber of the present invention is formed as a cavity bounded from above by a first punch surface 004, from below by a second punch surface 007, and to the sides by an inner surface 005. In this case, the punch surfaces 004 and 007 are both circular, and the inner surface 005 is cylindrical, and therefore the sintering chamber is cylindrical. Figure 1 There is no graphite layer positioned at the inner surface 005.

[0147] Figure 2 yes Figure 1The cross-sectional side view of the device, wherein the sintering chamber 013 is loaded and prepared for sintering. The sintering chamber 013 is limited to the side by the first punch surface 004 from above, the second punch surface 007 from below and the inner surface 005 of the die 006. The sintering chamber 013 therefore has a cylindrical shape. The sintering chamber 013 is filled with a plurality of particles for sintering. A plurality of particles can be tamped to be compacted after being introduced into the sintering chamber. A carbon material layer 014 is present at the inner surface 005 of the die 006. Therefore, the layer 014 in this embodiment constitutes a hollow cylindrical layer. In this case, the other layers 016 and 015 also made of carbon material are present at the second punch surface 007 and the first punch surface 004 respectively. The other layers 016 and 015 are optional. In practice, the lower layer 016 and layer 014 at the inside of the die 006 are first introduced to produce a recessed portion into which a plurality of particles can be filled. The particles are then compacted and an optional top layer 015 is placed on top. The punch surfaces (004, 007) are then moved inward to abut against the compacted particle disk coated with a graphite layer. For sintering, the punch surfaces (004, 007) are moved inward along the compression axis 011 as indicated by the arrows. The punch surfaces (004, 007) apply force to the particles, thereby generating pressure in the chamber. Current is applied across the sintering chamber 013 from an electrical power source 012 (between the first punch surface 004 and the second punch surface 007).

[0148] Figure 3 The steps of a method 200 for preparing a ceramic body are shown. In a first step a.201, a plurality of particles are provided. The particle size d 50 It can be, for example, 3 μm. An exemplary material for the particles is yttrium aluminum garnet (YAG). In a second step b.202, an apparatus as described in the present disclosure is provided. The sintering chamber of the apparatus can, for example, have a diameter of 500 mm. In a third step c.203, a plurality of particles are introduced into the sintering chamber of the apparatus. A graphite layer is introduced at the inner surface of the die before the particles. Optionally, a graphite layer can also be introduced at the second punch surface before the particles. A plurality of particles can be rammed to compact the particles into a cylinder. Optionally, the graphite layer for the first punch surface can be located at the top of the particles before being below the first punch surface. In a fourth step d.204, a pressure of, for example, 50 MPa is applied to the sintering chamber, and an electric current (e.g., 80 kA) is passed through the chamber to convert the particles into a product ceramic body.

[0149] Figure 4A cutaway cross section 300 of the sintering chamber 013 is shown. The cut is vertical, along the diameter of the sintering chamber 013, through the compression axis 011, to show the sintering chamber 013 from the side. The die 006 is a hollow cylinder with a wall thickness 302. A graphite layer 014 is applied to the inner surface 005 of the die 006 to form a concentric hollow cylinder with a thickness 301 (e.g., 2 mm). The die thickness 302, the layer thickness 301, and the diameter 303 of the sintering chamber 013 are each measured in a radial direction perpendicular to the compression axis 011.

[0150] Figure 5a and Figure 5b A core test 400 employed herein is shown. Figure 5a A perspective view before the test begins is shown. A coring tool 401 is positioned above a first flat surface 402 of a flat-form ceramic sample 406. In this case, the flat-form ceramic sample 406 is in the form of a cylindrical disk. The tool 401 is oriented along an axis perpendicular to the first flat surface 402. Arrow 408 shows the direction in which the tool 401 travels along the axis toward the flat-form ceramic sample 406. Once in contact with the flat-form ceramic sample 406, the coring tool 401 moves in a circular motion within a coring area 407, the diameter of which is greater than the diameter of the tip 409 of the coring tool 401. The circular motion is parallel to the first flat surface 402 and results in the removal of a cylindrical area from the flat-form ceramic sample 406. In addition, the geometric center 405 of the first flat surface 402 is also the geometric center 405 of the coring area 407. Figure 5b A cross-sectional view from the side during a core test is shown. Tool 401 has been advanced a distance 403 into a ceramic sample 406 of flat form having a sample thickness 404 . Figure 5b The coring tool 401 is shown having removed a cylindrical section 410 from a flat form ceramic sample 406. A distance 403 is determined between the first flat surface 402 and the end of the tool 401. The test ends when a crack is first observed in the flat form ceramic sample 406. The success level is determined as the ratio of the distance 403 of the core to the total thickness of the flat form ceramic sample 404 at the end of the test, expressed as a percentage.

[0151] Test Method

[0152] C Test

[0153] The sample ceramic of the flat form with the first flat surface and the thickness perpendicular to the first flat surface obtained in the embodiment is cored to determine whether there is excessive internal stress. The coring tool 401 is a 10mm diamond coring tool, for example, commercially available from Schott Diamantwerkzeuge GmbH, Stadtoldendorf, Germany. The tool is used in a commercially available CNC machine to cut a core in the part to be tested. The hole formed in the part by cutting the core is 56mm to 60mm, with a nominal diameter of 58mm. The core is cut by passing the tool 401 on the surface of the part in a spiral mode to drill a hole in the part. Suitable CNC machines that can be used for this test are available from, for example, DMG Mori Company Limited, Los Angeles, California, USA, such as its Ultrasonic 60eVo linear model. Another supplier of suitable CNC machines is Fair Friend Ent. Co. Ltd. in Taiwan, China, such as Feeler HV-1650 model. The test ends when the core extends all the way through the sample ceramic or when the sample ceramic is observed to fracture, whichever occurs first. The success score is given as a percentage of the thickness of the core cut in the sample to be tested. A success rating of 100% indicates low internal stress (if any); a success rating above 75% but below 100% indicates low internal stress; a success rating between 25% and 75% indicates corresponding to medium stress; and a success rating below 25% indicates high internal stress.

[0154] granularity

[0155] The particle size of the ceramic particles was determined using a laser scattering particle size distribution analyzer model LA-960 obtained from Horiba Scientific of Piscataway, New Jersey, USA.

[0156] Layer thickness

[0157] The thickness of the graphite layer can be measured by a physical measuring device, such as a caliper.

[0158] Density and theoretical density

[0159] The density of the ceramic body is measured according to standard ASTM B962-17. The theoretical density is calculated from X-ray diffraction (XRD) data. The unit cell parameters a, b and c are obtained from the XRD data. Using the unit cell parameters, the unit cell volume is calculated. Based on the crystal structure of the material, the number of molecular units present in each unit cell is determined. The molecular weight of the ceramic body is known because its chemical structure is known. Using the aforementioned data, the theoretical density is calculated as follows:

[0160] Theoretical density = (molecular weight x number of molecules per unit cell) / (volume of unit cell x Avogardo number)

[0161] Average grain size

[0162] The average grain size of the ceramic body is measured according to standard ASTM E112-13 (2021).

[0163] Example

[0164] The working of the invention will now be further elucidated with the aid of specific embodiments. The invention is not limited by the features of the embodiments, which are intended to provide specific concrete implementations of the invention.

[0165] Example A

[0166] according to Figure 1 The schematic diagram shown provides an apparatus. The die has a height of 1 m, and the punches each have a circular punch surface with a diameter of 650 mm. The sintering chamber correspondingly has a cylindrical shape with a cross-sectional diameter of 650 mm. The graphite layer on the inner surface of the die is a 1.9 mm total thickness graphite available from Neograf Solutions of Lakewood, Ohio. GTA Flexible Graphite. Neograf Solutions offers flexible graphite in sheet form with thicknesses of 0.13mm, 0.25mm, 0.38mm, 0.51mm, 0.64mm and 0.76mm. In this example, two 0.76mm sheets and one 0.38mm sheet were used for a total thickness of 1.9mm.

[0167] The particle size d 50 Commercially available yttrium oxide and aluminum oxide powders of 3 μm were mixed together and 5 kg of the mixture was introduced into the sintering chamber, spread to an approximate horizontal height and compacted with a force of about 40 tons to a compaction height of 20 mm. After sintering, the powder mixture formed yttrium aluminum garnet (YAG). Next, a mixture of commercially available powders was introduced into the sintering chamber in an amount of 27 kg to produce zirconium oxide toughened alumina (ZTA) when sintered and spread to an approximately uniform height of about 100 mm. Finally, a mixture of powders for forming YAG and ZTA was introduced into the sintering chamber in an amount of 7 kg and spread to an approximately uniform height of about 30 mm.

[0168] The punch moves inward to reach Figure 2The position shown. A force is applied to the powder in the sintering chamber by the first punch and the second punch to reach a sintering chamber pressure of about 15MPa. 40kA to 70kA supplied via the punch is passed through the sintering chamber for a total of 9 to 10 hours. The product is a cylindrical ceramic disc in flat form with a diameter of about 650mm and a thickness of about 26mm. The example is repeated with the following thicknesses of the graphite layer on the inner surface of the die: 0.5mm, 1mm, 1.3mm, 1.5mm, 2.5mm, 5mm, 10mm and 20mm.

[0169] Although the above-described embodiments are three-layer cylindrical ceramic disks, the methods disclosed herein are also applicable to such disks in single-layer and double-layer forms.

[0170] Example B

[0171] Example A was repeated, but the circular diameter of the punch surface was 100 mm.

[0172] Example C

[0173] Example A was repeated, but the circular diameters of the punch surface were 200 mm, 350 mm and 800 mm respectively.

[0174] result

[0175] The results of Example A are shown in Table 1.

[0176]

[0177]

[0178] Table 1

[0179] The results of Example B are shown in Table 2

[0180]

[0181] Table 2

[0182] When considering the results of Table 2, the following can be seen: When considering the scale-up from producing 100 mm ceramic bodies to producing 650 mm ceramic bodies, there is no indication from the results of Table 2 that the layer thickness should be changed in order to produce 650 mm ceramic bodies of sufficient quality.

[0183] The 200 mm diameter embodiment was similar to the 100 mm diameter embodiment, i.e., 100% success was achieved on the plate in the core test, and the energy consumption was uniform up to and including a layer thickness of 2.5 mm. The results for the 350 mm diameter were similar to the 650 mm diameter results, except that the core test at 1.5 mm was 100% successful. The results for the 800 mm diameter were similar to the 650 mm diameter results, except that crushing was observed in the core test at 1 mm thickness, and the power supply was insufficient to sinter the product in the 5 mm and 10 mm thickness tests.

[0184] Reference List

[0185] 001 First Propulsion Device

[0186] 002 First Piston

[0187] 003 First Punch

[0188] 004 First punch surface

[0189] 005 Inner surface

[0190] 006 Die Head

[0191] 007 Second punch surface

[0192] 008 Second Punch

[0193] 009 Second Piston

[0194] 010 Second propulsion device

[0195] 011 Compression axis

[0196] 012 Electric power source

[0197] 013 Sintering Chamber

[0198] 014th floor

[0199] 015,016 Additional Layers

[0200] 200 Preparation method of ceramic body

[0201] 201 Step a.

[0202] 202 Step b.

[0203] 203 Step c.

[0204] 204 Step d.

[0205] 300 Cross section of a sintering chamber

[0206] 301 Layer Thickness

[0207] 302 die thickness

[0208] 303 Sintering chamber diameter

[0209] 400-core test setup

[0210] 401 Coring Tools

[0211] 402 first flat surface

[0212] 403 Drilling depth

[0213] 404 Sample thickness

[0214] 405 Geometric Center

[0215] 406 Ceramic samples in flat form

[0216] 407 Coring Area

[0217] 408 perpendicular to the direction of motion of the flat ceramic sample

[0218] 409 Tip of coring tool

[0219] 410 Cylindrical section removed from a flat ceramic sample

Claims

1. A device having a sintering chamber (013), the sintering chamber (013) being defined by the following device components: i. a first punch surface (004) of a first punch (003); ii. a second punch surface (007) of a second punch (008); and iii. the inner surface (005) of the die (006); in: The punch (003, 008) is adapted and arranged to apply a pressure of at least 1 MPa to the target in the sintering chamber (013) along a compression axis (011); The first punch (003) and the second punch (008) are connected to an electrical power source (012) adapted and arranged to provide an electric current of at least 5 kA; The first punch and the second punch (003, 008) comprise at least 50 wt% carbon based on the total weight of the punch (003, 008); The sintering chamber (013) has a cross-sectional width W of at least 300 mm perpendicular to the compression axis (011); wherein a carbon material C is present on at least a portion of the inner surface (005) of the die head (006) δ A layer δ having an average thickness D determined on the inner surface (005) of the die (006) δ , Where D δ In the range of 1.1mm to 8mm.

2. The device according to claim 1, wherein the thickness D of the layer δ determined on the inner surface (005) of the die (006) is δ The standard deviation is in the range of 0.01 mm to 0.08 mm.

3. The device according to claim 1 or 2, wherein the layer δ consists of 2 or more stacked sub-layers.

4. Device according to any of the preceding claims, wherein the two punches (003, 008) and the die (006) are at least partially present in a vacuum chamber or in a non-oxidizing atmosphere or both.

5. The device according to any of the preceding claims, wherein the sintering chamber (013) has a diameter D C , and the diameter D C With the layer D δ The average thickness ratio D C :D δ In the range of 100:1 to 350:

1.

6. The device according to any one of the preceding claims, wherein one or both of the following are satisfied: a. There is a carbon material C at at least a portion of the first punch surface (004) ε The layer ε; b. Carbon material C exists at at least a portion of the second punch surface (007) θ The layer θ.

7. The device according to any one of the preceding claims, wherein one or more of the following are satisfied: a. The first punch (003) comprises at least 99 wt % carbon, based on the total weight of carbon atoms in any chemical form and the total weight of the first punch (003); b. The second punch (008) comprises at least 99 wt% carbon, based on the total weight of carbon atoms in any chemical form and the total weight of the second punch (008); c. the die (006) comprises at least 99 wt% carbon, based on the total weight of carbon atoms in any chemical form and the total weight of the die (006); d. The layer δ comprises at least 99 wt% carbon, based on the total weight of carbon atoms in any chemical form and the total weight of the layer δ.

8. The device according to any one of the preceding claims, wherein the die head is made of a carbon material Cγ and satisfies one or more of the following: C δ and C γ With different anisotropy values, B δ and C γ having different specific conductivities determined in a direction parallel to said compression axis (011), C δ and C γ having different specific conductivities determined in a direction perpendicular to the inner surface (005), dC δ and C γ having different specific thermal expansion rates determined in a direction parallel to said compression axis (011), eC δ and C γ having different specific thermal expansion rates determined in a direction perpendicular to said inner surface (005), f. The first carbon material and the second carbon material have different ash contents as determined by ASTM C-561].

9. A method for preparing a ceramic body, the method comprising the steps of: a. Providing multiple particles; b. Providing a device according to any one of the preceding claims; c. introducing the particles into the sintering chamber (013) of the device; d. applying a pressure P in the range of 1 MPa to 80 MPa and an electric current I in the range of 1 kA to 100 kA to obtain the ceramic body.

10. The method of claim 9, wherein the particles comprise at least 30% by weight of yttrium in any chemical form, based on the total mass of yttrium atoms and the total mass of the particles.

11. A ceramic body obtainable by a process according to claim 9 or 10.

12. The ceramic body according to claim 11, wherein at least one or all of the following are satisfied: a. The value of density divided by theoretical density is less than 1.0; b. The average grain size is less than 5μm; c. The standard deviation of the average grain size distribution is in the range of 1.8±2 μm to 2.2±2 μm.

13. A component comprising a ceramic body according to claim 11 or 12.

14. The assembly of claim 13, wherein the assembly is selected from the group consisting of: a. Plasma etcher, b. Plasma processing chamber (etching or deposition method), c. Wear-resistant plates for load bearing, d. Mill lining of grinding mill.

15. Use of a graphite layer having a thickness in the range from 1.1 mm to 8 mm for producing a ceramic body having an extension of at least 300 mm by spark plasma sintering.